2008
DOI: 10.1177/030802260807101206
|View full text |Cite
|
Sign up to set email alerts
|

Using Theory to Underpin an Integrated Occupational Therapy Service through the Canadian Model of Occupational Performance

Abstract: The aim of this action research study was to embed the theoretical tenets of the Canadian Model of Occupational Performance and its structures in a way that was appropriate to, and would be used by, all staff within an integrated health and social care setting. The action research involved 10 phases of reflection and action, with data analysis occurring between the cycles. The findings showed the importance of taking time to embed theory before implementing model structures in order to prevent those structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…This view is consistent with Boniface et al's (2008) statement that "Occupational therapy should demonstrate its theory through its practice" (p. 537) in order for occupational therapy practitioners to cement their professionalism. Ikiugu (2012) also observed that unqualified acceptance of EBP without evaluation of evidence to ensure that it validates the profession of occupational therapy could be detrimental to its unique identity.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This view is consistent with Boniface et al's (2008) statement that "Occupational therapy should demonstrate its theory through its practice" (p. 537) in order for occupational therapy practitioners to cement their professionalism. Ikiugu (2012) also observed that unqualified acceptance of EBP without evaluation of evidence to ensure that it validates the profession of occupational therapy could be detrimental to its unique identity.…”
supporting
confidence: 84%
“…Unfortunately, deemphasis of theory as a guide to practice may be detrimental to the well-being of the profession (Hinojosa, 2013). Use of theory to inform decision-making is what differentiates professionals from non-professionals (Boniface et al, 2008). Therefore, competent occupational therapy practitioners should be ready and able to explain how they use the profession's theoretical conceptual practice models to inform their clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The new vision is true to the profession's philosophical base (Boniface et al, 2008) and aligns with the World Health Organization's (2002) emphasis on re-orientating health services to address participation outcomes. For occupational therapy, one risk of not responding to the challenge to reform and re-vision practice is that the hegemonic ideas emanating from medical, scientific and fiscal discourses that currently dominate health and social care settings (Wilding, 2011) will continue to shape and constrain the profession.…”
Section: Introductionmentioning
confidence: 94%
“…In the UK, Boniface et al (2008) achieved some success in a 4-year-long programme. This involved 270 therapists in the decision to adopt a new model of practice, by providing existing and new therapists with a formal 1-day training opportunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation